Scaling Behavior of Bulk Freight Rate Volatility Before and After Noise Reduction - 代思宇 陈飞儿 曾亚东 曾鑫 (Shanghai jiao tong da xue xue bao, 2016)
Analysis of freight rate volatility characteristics is a hot topic after year 2008 due to the effect of financial crisis in marine transportation. In this paper, we analyze the bulk freight rate index by detrended fluctuation analysis （DFA） method and discover the scaling behavior. Switching points （SPs）, as the indicators of scaling behavior, can be eliminated after Vondrak noise reduction technique. Therefore, we conclude that high- frequency noise is the cause of SP.